2012
DOI: 10.1093/schbul/sbs105
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy for Subjects at Ultrahigh Risk for Developing Psychosis: A Randomized Controlled Clinical Trial

Abstract: Compared with TAU, this new CBT (focusing on normalization and awareness of cognitive biases) showed a favorable effect on the transition to psychosis and reduction of subclinical psychotic symptoms in subjects at UHR to develop psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
183
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(191 citation statements)
references
References 33 publications
6
183
1
1
Order By: Relevance
“…9 Both our 18-month follow-up results 9 and our 4-year follow-up results 10 demonstrated a favorable effect on reducing the incidence of psychosis by ±50% compared with routine care (RC) alone.…”
Section: In the Dutch Early Detection Intervention And Evaluation Trimentioning
confidence: 68%
See 2 more Smart Citations
“…9 Both our 18-month follow-up results 9 and our 4-year follow-up results 10 demonstrated a favorable effect on reducing the incidence of psychosis by ±50% compared with routine care (RC) alone.…”
Section: In the Dutch Early Detection Intervention And Evaluation Trimentioning
confidence: 68%
“…Besides the proportion of averted transitions to psychosis, 9,35 the difference in QALYs showed a clinically relevant but statistically nonsignificant effect of the intervention on the lives of at-risk individuals and at least no deterioration in their health-related quality of life.…”
Section: Clinical and Public Health Relevancementioning
confidence: 97%
See 1 more Smart Citation
“…In addition, patients should be informed that these phenomena are commonly present in the context of depression and may have a negative impact on course and outcome. Research has shown that psycho-education or simply discussing psychotic experiences reduces their stressful effects (van der Gaag et al 2012), which in turn may be beneficial for recovery. Electroconvulsive therapy or antipsychotic medication may need to be considered or, alternatively, cognitive behavioural therapy or other psychotherapeutic approaches may be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been inconsistent findings when CBT interventions have been compared with treatment as usual for children and adolescents at risk for psychosis. One study found a significant difference [22] while the findings of another study indicated no improvement in either group [23]. There have also been no studies of the efficacy of psychodynamic psychotherapy with psychotic children and youth in spite of the use of psychodynamic principles in the understanding psychotic communication.…”
Section: Need For Research On Psychotherapy and Supportive Interventionsmentioning
confidence: 99%